Spirometric and gas transfer measurements among normal adult South African men : an investigation into anthropoemtric, socio-economic, racial and environmental factors influencing lung function - Goldin, Jonathan Gerald (Department of Medicine, 2020)
An investigation into anthropocentric, socio-economic, racial and environmental factors influencing lung function. In modern clinical practice the data derived from pulmonary function tests are an integral part of the evaluation of pulmonary disease states. Such data may shed light on the nature of the disease state, the extent (severity) of the disease and the degree of functional impairment that is present. It is generally recognized that there is a lack of consistent data regarding "normal" values in pulmonary function. Despite great progress in standardizing instrumentation, methodology and calculation of the lung function test, the interpretation of the test is complicated by the lack of standardized prediction values. The identification of race as a confounding variable is particularly important in an evaluation of appropriateness of currently used pulmonary function reference values. It has been pointed out that reference values for blacks, in particular, have deficiencies and that this issue demands urgent investigation. The study of differences in lung function in different race groups is complex. Race, itself, is a controversial concept and its close relationship to social stratification needs to be explored before differences may be attributed to race itself.